If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(5x+7)=(3x+4)=55
We move all terms to the left:
5(5x+7)-((3x+4))=0
We multiply parentheses
25x-((3x+4))+35=0
We calculate terms in parentheses: -((3x+4)), so:We get rid of parentheses
(3x+4)
We get rid of parentheses
3x+4
Back to the equation:
-(3x+4)
25x-3x-4+35=0
We add all the numbers together, and all the variables
22x+31=0
We move all terms containing x to the left, all other terms to the right
22x=-31
x=-31/22
x=-1+9/22
| X+(x+39x)+(13-x)=966 | | x+2x+3+(1/2x)=11 | | 6x-90/8=3x | | 11x-3x+14=10 | | -15(2x-3)=75 | | 2x-24=-34 | | 24-2x=-34 | | 9/10+(4/5x)=4x | | 9/10(4/5x)=4x | | 4x+2+x-14=180 | | 3x+7=3(7x-6)+97 | | 3/8(x+8)=1/2(x+5) | | 9/10+4/5x=4x | | 1/4x^2+3=52 | | 3(2x-4)+4(3x+6)=66 | | 11(6-y=231 | | 20x-4=40 | | 17/10x=4x | | 4(3x-6)-5x+8=5 | | (9/10x)+(4/5x)=4x | | .9x+4/5x=4x | | x+8.2=3.4 | | 3x=-5x-32 | | 4/3x+7=2.5x | | 2.5(x+31)+0.8x=226 | | (2.5x+31)+0.8x=226 | | -4y+9(6y-3)=-2-2(3-y) | | 1/3(4x+7)=2.5x | | x(6+9)=3x+55 | | x/2+6=x/2+10 | | -3x-(5x-5)=17-4x | | 3(4x-5)=-63 |